Improvement of Selected Quality and Safety Traits in Turmeric-Enriched Kale Pesto Using Blue Light and Sous-Vide - Magdalena A. Olszewska; Anna Draszanowska; Aleksandra Zimińska; Małgorzata Starowicz (Molecules)
The potential of blue light (BL) and sous-vide (S-V) as a novel approach for food preservation was investigated via measurements of the total phenolic content (TPC), antioxidative activity, color, and their antibacterial effect on Listeria monocytogenes in two versions of laboratory-prepared kale pesto, with and without the addition of turmeric. The TPC ranged from 85 to 208 mg/100 g GAE d.m. and 57 to 171 mg/100 g GAE d.m., respectively. In both versions, the highest TPC was in the blue light–sous-vide samples, while the lowest was after the sous-vide, with a loss of polyphenols of almost 40% during storage when turmeric was absent. Antioxidative capabilities of the pesto were initially estimated at 54.07 and 7.46 µmol TE/g d.m., respectively, indicating significant bioactivity enhancement by turmeric. In turmeric-enriched pesto, sous-vide decreased the antioxidative activity levels by 12% in fresh pesto and by 45% during storage. Meanwhile, blue light compensated for the losses caused by the sous-vide treatment. Although the hue angle (h°) of sous-vide pesto was lower than that of blue light pesto in most samples, sequential BL and S-V ultimately yielded the lowest h°. The sequential BL and S-V treatment resulted in a 1.7 log reduction in the L. monocytogenes population, whereas adding turmeric increased the treatment efficacy by another 2.0 logs. Thus, as a source of photosensitizing molecules, turmeric was highly antibacterial after photothermal activation with blue light and sous-vide. This study suggests that blue light could be an effective (pre)treatment used on pesto sauces to preserve bioactivity and to improve safety when enriched with a natural additive like turmeric.